Integrated coupling of road traffic and network simulation for realistic emulation of connected vehicle applications. (May 2016) - Sun, Jian; Yang, Yuwei; Li, Keping
To meet the requirements of connected vehicle (CV) system simulation evaluations, different simulators (i.e., traffic flow simulation, network communication simulation and CV application simulation) must be combined and interaction must be enabled among them during the run-time of the simulation. This paper proposes a CV simulation prototype system based on integration of three components in one coupling. Considering the characteristics of the distributed interactive simulation of multi-emulators, a high-level architecture simulation and modeling concept is used to construct the simulation framework, and the three types of simulation elements are defined as the primary federates. The integration simulation system is constructed by defining the federation object model and developing the support environment of the run-time infrastructure during simulation. In the simulation implementation procedure, a commercial-off-the-shelf time-stepped VISSIM simulator and an open-source event-driven NS2 simulator are selected as the basic simulation tools to develop the system. In addition, selected related technologies are investigated, including the NS2 simulation model transformation, time synchronization management strategy, track consistency strategy, and integration of application members. Finally, two case studies of intersection speed guidance and collision warning are used to verify the validity of the simulation prototype system.